The Protection of Privacy in the Workplace: A Comparative Study - Gondwe, Mimmy (Stellenbosch University, 2011)
The importance of privacy lies in the fact that it represents the very idea of human dignity or the preservation of the ‘inner sanctum’. Not surprisingly, however, operational concerns of employers and technological developments combine continuously to challenge the preservation of privacy in the workplace. Employees the world over are exposed to numerous privacy invasive measures, including drug testing, psychological testing, polygraph testing, genetic testing, psychological testing, electronic monitoring and background checks. Hence, the issue at the heart of this dissertation is to determine to what extent privacy is protected in the South African workplace given advancements in technology and the implications (if any) for the right to privacy as such. A secondary aim of the dissertation is to attempt to provide a realistic balance between the privacy concerns of employees and the operational needs of employers in this technological age. As such the main focus of dissertation falls within the sphere of employment law. In order to provide an answer to the research issue discussed above, the dissertation addresses five ancillary or interrelated issues. First, the broad historical development of the legal protection of privacy is traced and examined. Second, a workable definition of privacy is identified with reference to academic debate and comparative legislative and judicial developments. Third, those policies and practices, which would typically threaten privacy in the employment sphere are identified and briefly discussed. Fourth, a detailed evaluation of the tension between privacy and a number of selected policies and practices in selected countries is provided. More specifically, the dissertation considers how these policies and practices challenge privacy, the rationale for their existence and, if applicable, how these policies and practices – if necessary through appropriate regulation – may be accommodated while simultaneously accommodating both privacy and the legitimate concerns of employers. The selection of these practices and policies is guided by two considerations. At the first level the emphasis is on those challenges to privacy, which can be traced back to technological developments and which, as such, foster new and unique demands to the accommodation of privacy in the workplace. The secondary emphasis is on those policies, which are representative of the fundamental challenges created by new technologies to privacy. To effectively address the above issues the dissertation uses the traditional legal methodology associated with comparative legal research, which includes a literature review of applicable law and legal frame work and a review of relevant case law and a comparative study of selected foreign jurisdictions.
Keywords: Privacy infringements; Privacy protection; Right of privacy

Public employment and the relationship between labour and administrative law - Loots, Barbara Evelyn (University of Stellenbosch, 2011)
The focus of this study is the rights-based normative overlap of labour and administrative law in public employment. As the judiciary appeared to be unable to agree on a unified approach to the application of the rights to fair labour practices and just administrative action to public employment, it was clear that the complexity and multi-dimensional character of the debate required analysis of existing approaches to the regulation of the public employment relationship. The following initial research question was formulated: To what extent does (and should) the constitutionalised rights to fair labour practices (s 23) and just administrative action (s 33) simultaneously find application in the regulation of public employment relationships? In answering this question, certain realities had to be acknowledged, the most important being that the debate in question jurisprudentially revealed itself to be a jurisdictional turf-war between the Labour and High Courts, rather than proper consideration of the relevant substantive arguments and underlying normative considerations. This called for an additional dimension to be added to the research question, namely consideration of the extent to which the ss 23 and 33 rights are informed by variable and possibly different normative principles and whether these rights allow for cooperative regulation of public employment in accordance with the doctrine of interdependent fundamental rights. This became the primary focus of the study. In an attempt to simplify the debate, a deliberate decision was taken to limit the scope of the normative study to South Africa with its own historic influences, structures and constitutional considerations. The study shows that both labour and administrative law (as constitutionally informed) share concern for equity-based principles. This is evident from the flexible contextually informed perspectives of administrative law reasonableness in relation to labour law substantive fairness, as well as a shared concern for and approach to procedural fairness. Once simplified, and in the absence of any undue positive law complexity, the public employment relationship, at both a normative and theoretical level, furthermore shows no substantive status difference with private employment relationships. It is, however, accepted that there are job and sector-specific contextual differences. In the absence of substantive normative conflict between these branches of law and in the absence of a fundamental (as opposed to contextual) difference between public and private employment, there appears to be no reason to ignore the constitutional jurisprudential calls for hybridity, otherwise termed the doctrine of interdependence. The idea of normatively interdependent rights expresses the Constitution’s transformative vision (through the idea of flexible conceptual contextualism) and recognises that human rights may overlap. This also means that where such overlap exists, rights should be interpreted and applied in a mutually supportive and cooperative manner that allows for the full protection and promotion of those rights. In giving expression to the interdependent normative framework of constitutional rights, these norms (absent any substantive rights-based conflict) should then be used by the judiciary as an interpretative tool to align specific labour law and general administrative law in the regulation of public employment relationships.
Keywords: Administrative law; Employment law; Labour law